From Knowing to Doing—From the Academy to Practice; Comment on “The Many Meanings of Evidence: Implications for the Translational Science Agenda in Healthcare” - Jo Rycroft-Malone (International Journal of Health Policy and Management, 2014)
In this commentary, the idea of closing the gap between knowing and doing through closing the gap between academics and practitioners is explored. The two communities approach to knowledge production and use, has predominated within healthcare, resulting in a separation between the worlds of research and practice, and, therefore, between its producers and users. Meaningful collaborations between the producers and users of research could in theory, create the conditions for more situated knowledge production and use, and result in a potential reduction in the evidence-practice divide within a health service context.